2014
DOI: 10.1177/0954407014531246
|View full text |Cite
|
Sign up to set email alerts
|

Control of the motorized active suspension damper for good ride quality

Abstract: This paper presents a control algorithm for the motorized active suspension damper. The control algorithm consists of supervisory, upper-level and lower-level controllers. The supervisory controller determines the control modes, such as the passive mode, the roll mode and the body acceleration mode. The upper-level controller computes the damping force using linear quadratic control theory. The actuator input is determined by the lower-level controller. Three state estimators, namely the vehicle body’s velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 11 publications
(9 reference statements)
0
20
0
Order By: Relevance
“…12 The dynamic friction and the actuator delay lead to a significant increase in the power consumption and also degrade the performance of the actuator, thus resulting in a deterioration in the energy efficiency.…”
Section: Mode Controlmentioning
confidence: 99%
“…12 The dynamic friction and the actuator delay lead to a significant increase in the power consumption and also degrade the performance of the actuator, thus resulting in a deterioration in the energy efficiency.…”
Section: Mode Controlmentioning
confidence: 99%
“…Lack of effective research results motivates this Yi et al [6] proposed a system to control semi-active suspensions since it has advantages of both active and passive suspensions. It is well known that semi-active suspensions provide better ride comfort compared to passive suspensions and more affordable with less energy consumption than active suspensions [7]. Even though these aspects, semi-active system performance cannot be equivalent to active systems.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that Intensive research has been done in order to validate half car suspension control algorithm [7], [11]. The authors in [7] conducted simulations by implementing half car control algorithm into just rear half of the passenger vehicle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suspension system plays an important role in providing a high level of ride comfort by isolating the vehicle body from road irregularities and improving road holding capacity by preventing the wheel from loosing road contact [1][2][3]. It is well known that these are conflicting requirements and many studies have shown that this conflict can be eased by using controlled suspension systems instead of passive ones [4,5].…”
Section: Introductionmentioning
confidence: 99%